Pelatihan Path Analysis Terhadap Guru SMK Di Jakarta Timur - Erlando Doni Sirait; Dwi Dani Apriyani; Vickry Ramdhan; Umar Wirantasa; Fajar Erlangga (CV. Multi Kreasi Media, 2025)
The limited ability of vocational high school (SMK) teachers in East Jakarta to apply advanced statistical analysis has resulted in low-quality educational research outputs. Therefore, this community service program aims to enhance teachers’ competence in understanding and applying path analysis using the SPSS statistical software. The program was implemented through four main stages: preparation, core implementation, mentoring, and evaluation. The adopted approach combined lectures, workshops, hands-on practice, and mentoring to equip participants with both conceptual understanding and practical skills. The results showed a significant improvement in teachers’ abilities, with more than 80% of participants able to explain the basic concepts of path analysis and independently perform data processing. Participants also successfully produced simple analytical reports based on simulated data, reflecting their increased research skills. Based on evaluation results and positive participant responses, the training method proved to be effective and applicable in supporting data-driven research among SMK teachers in East Jakarta. This activity is expected to serve as an initial step in fostering a culture of data-based research within vocational schools and to encourage teachers to further develop their research capacity through advanced training and inter-school collaboration.